2016
DOI: 10.1214/16-aos1480
|View full text |Cite
|
Sign up to set email alerts
|

Global rates of convergence in log-concave density estimation

Abstract: The estimation of a log-concave density on R d represents a central problem in the area of nonparametric inference under shape constraints. In this paper, we study the performance of log-concave density estimators with respect to global loss functions, and adopt a minimax approach. We first show that no statistical procedure based on a sample of size n can estimate a log-concave density with respect to the squared Hellinger loss function with supremum risk smaller than order n −4/5 , when d = 1, and order n −2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 38 publications
2
109
0
Order By: Relevance
“…Proposition 5.2 can also be seen as providing bounds for the variance of a log-concave variable. See Kim and Samworth [2014], section 3.2, for some further results of this type.…”
Section: Regularity and Approximations Of Log-concave Functionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Proposition 5.2 can also be seen as providing bounds for the variance of a log-concave variable. See Kim and Samworth [2014], section 3.2, for some further results of this type.…”
Section: Regularity and Approximations Of Log-concave Functionsmentioning
confidence: 97%
“…They show that the MLE exists and is Hellinger consistent. Doss and Wellner [2013] have obtained Hellinger rates of convergence for the maximum likelihood estimators of log-concave and s –concave densities on ℝ, while Kim and Samworth [2014] study Hellinger rates of convergence for the MLEs of log-concave densities on ℝ d . Henningsson and Astrom [2006] consider replacement of Gaussian errors by log-concave error distributions in the context of the Kalman filter.…”
Section: Some Open Problems and Further Connections With Log-concamentioning
confidence: 99%
“…Dümbgen & Rufibach (2009) found that its rate of convergence with respect to the supremum norm on a compact interval is at least (log(n)=n) 1=3 . Kim & Samworth (2016) established that it achieves the minimax optimal rate with respect to squared Hellinger loss. Kim, Guntuboyina & Samworth (2017) further showed that it achieves a faster rate of convergence when the logarithm of the true density is made up of k affine pieces, or is close to being so.…”
Section: Introductionmentioning
confidence: 99%
“…Their nonparametric maximum likelihood estimators were studied by Dümbgen & Rufibach (2009), Cule et al (2010), Cule & Samworth (2010), Chen & Samworth (2013), Pal et al (2007) and Dümbgen et al (2011) (referred as [DSS 2011] thereafter). The convergence rates of these estimators for log-concave densities were studied by Doss & Wellner (2013) and Kim & Samworth (2014). Such estimators provide more generality and flexibility without any tuning parameters.…”
Section: Introductionmentioning
confidence: 99%